Examination of thyme leaves grown under different spectra - Mazikowski, Adam; Feldzensztajn, Mateusz (Photonics Letters of Poland, 2023)
Nowadays artificial light is often used in horticulture. Proper light composition may have significant impact on plant properties, important from the consumer's point of view. Based on experimental cultivation of thyme, examination of thyme leaves grown under different spectra was performed. Transmissive spectra, colorimetric properties, dry mass yield as well as biometrical properties (shape of leaves) were determined. Attention to the issues of energy efficacy of light sources was also paid. Full Text: PDF References D.L. DiLaura, K.W. Houser, R.G. Mistrick, G.R. Steffy, The lighting handbook, Illuminating Engineering Society, 2011. DirectLink CREE Inc, Cree® 2835 LEDs Product family datasheet, (accessed 19 february 2023). CrossRef DirectLink M. Gilewski, "The role of light in the plants world", Phot. Lett.Pol., 11, 115 (2019). CrossRef J. Yan, H. Liu, W. Zhao, Y. Su, "Photon flux calibration of LED in horticulture lighting", Proc. SPIE 12319(2022). CrossRef B. Purabi, V.K. Venugopalan, R. Nath, P.K. Chakraborty, A. Gaber, W.F. Alsanie, B.M. Raafat, A. Hossain. 2022. "Seed Priming and Foliar Application of Nutrients Influence the Productivity of Relay Grass Pea (Lathyrus sativus L.) through Accelerating the Photosynthetically Active Radiation (PAR) Use Efficiency" Agronomy 12, 1125 (2022). CrossRef T. Hegemann, J. Balasus, Q. Trinh, A. Herzog, T. Khanh, "Using spectral sensors to determine photosynthetic photon flux density in daylight - A theoretical approach". Light Res. Technol. 54, 429 (2022). CrossRef R.J. Ritchie, "Modelling photosynthetic photon flux density and maximum potential gross photosynthesis", Photosynthetica 48, 596 (2010). CrossRef D. Kulpa, A. Wesolowska, P. Jadczak, "Micropropagation and Composition of Essentials Oils in Garden Thyme (Thymus vulgaris L.)" Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 46, 525 (2018). CrossRef V. R. Affonso, H.R. Bizzo, C.L.S. Lage, A. Sato, "Influence of Growth Regulators in Biomass Production and Volatile Profile of in Vitro Plantlets of Thymus vulgaris L", J. Agric. Food Chem., 57, 6392 (2009) CrossRef W. Letchamo ,A. Gosselin, "Transpiration, essential oil glands, epicuticular wax and morphology of Thymus vulgaris are influenced by light intensity and water supply", J. Hortic. Sci, 71 (1996). CrossRef M. Feldzensztajn,, P. Wierzba, A. Mazikowski, "Examination of Spectral Properties of Medicinal Plant Leaves Grown in Different Lighting Conditions Based on Mint Cultivation", Sensors, 21, 4122 (2021) CrossRef H. Spalholz, P. Perkins-Veazie, R. Hernández, "Impact of sun-simulated white light and varied blue:red spectrums on the growth, morphology, development, and phytochemical content of green- and red-leaf lettuce at different growth stages". Sci. Hortic., 264, 109195 (2020). CrossRef J.M. Tabbert, H. Schulz, A. Krähmer., "Increased Plant Quality, Greenhouse Productivity and Energy Efficiency with Broad-Spectrum LED Systems: A Case Study for Thyme (Thymus vulgaris L.)", Plants 10, 960 (2021). CrossRef